Life cycle cost and sensitivity analysis of reutealis trisperma as non-edible feedstock for future biodiesel production - Riayatsyah T.M.I.; Ong H.C.; Chong W.T.; Aditya L.; Hermansyah H.; Mahlia T.M.I. (MDPI AG, 2023)
Biodiesel; Cost accounting; Cost benefit analysis; Costs; Economic analysis; Feedstocks; Investments; Seed; Sensitivity analysis; Taxation; Well stimulation; Biodiesel production; Biofuel economies; Implementation aspects; Lifecycle costs; Non-edible oil; Reutealis trisperma; Second generation; Technical barriers; Life cycle